2020
DOI: 10.1002/iir.1381
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of company voluntary arrangements: Success, failure and proposals for reform

Abstract: Company Voluntary Arrangements (CVAs) are designed to be used in the UK to rescue a company as a going concern. They are under used in practice and have a reputation for high failure rates. This article, based upon a longer report funded by the UK insolvency profession, considers the nature of success or failure of CVAs. It considers empirical evidence to identify the weak points of CVAs in practice. It looks at quantitative data as well as taking into account views of practitioners and other stakeholders. Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the UK, a popular but relatively often unsuccessful procedure is the so-called CVA (Company Voluntary Agreements). A study of 552 companies that initiated the above procedure in 2013 found that as many as 360 proceedings failed at an early stage (Walton et al 2020). Based on a survey of practitioners carried out by the same authors in 2017, it was found that:…”
Section: Literature Backgroundmentioning
confidence: 99%
“…In the UK, a popular but relatively often unsuccessful procedure is the so-called CVA (Company Voluntary Agreements). A study of 552 companies that initiated the above procedure in 2013 found that as many as 360 proceedings failed at an early stage (Walton et al 2020). Based on a survey of practitioners carried out by the same authors in 2017, it was found that:…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Jostarndt, Sautner (2010). 17Camacho-Miñano et al (2015).18 Laitinen (2008Laitinen ( ), (2011;Lukason, Urbanik (2013).19 Walton et al (2020).20 Restructuring law of 15 May 2015, consolidated text: Journal of Laws of the Republic of Poland [JL] 2015, item 978.…”
mentioning
confidence: 99%